Corrosion Behavior of Aluminum-Forming Alloy 310S for Application in Molten Chloride Salt CSP Thermal Storage Tank - Wei, Ying; La, Peiqing; Jin, Jing; Du, Mingchen; Zheng, Yuehong; Zhan, Faqi; Sheng, Jie; Yu, Haicun; Zhu, Min (Frontiers in Materials, 2022)
The key of the new generation of solar thermal power plant is to increase the operating temperature of molten salt to 800 ℃, and change the heat transfer medium from nitric acid mixed salt to chlorine mixed salt, so as to significantly reduce the cost of power generation. Therefore, the alloy material resistance to high temperature and fusible chloride salt is one of the core technologies for the successful implementation of Concentrated Solar Power（CSP）technology. In this study, the alumina-forming alloy（AFA）310S for heat storage tank was prepared by aluminum-thermal reaction casting method. The hot corrosion behavior and mechanism of AFA 310S in chloride molten salt at 800 ℃ were studied by static immersion etching for 600 h. AFA 310S exhibits good thermal corrosion properties in KCl 20.4 wt. % + MgCl2-55.1 wt. % + NaCl 24.5 wt. %. The results indicate that，compared with commercial 310S, AFA 310S has better oxidation resistance at 800 ℃. At the initial stage of corrosion, dense Cr2O3 and continuous Al2O3 passivation films are formed. At the same time, MgO-rich oxidation products were produced in the outermost layers of the two alloys during the 600 h process. Over time, however, the damage caused by chlorine became more apparent, mainly due to the “oxidation-chlorination” process of the metal. A large number of cavities and cracks on the surface are formed, and the oxide layer has obvious spalling. When Al element was added into the alloy, the dense passivation film could be formed after 120 h of corrosion with the stronger corrosion resistance. The experiment simulated the corrosion behavior in the worst environment, such as in air, unoxidized alloy, molten salt without corrosion inhibitor, etc. By weight loss calculation, commercial 310S plate is completely unsuitable for Concentrated Solar Power plant. The corrosion rates of the two alloys are compared as follows: commercial 310S > AFA 310S. To sum up, AFA 310S has a good application prospect in Concentrated Solar Power.